La presa in carico del paziente psichiatrico in comunità - Moinzadeh Giortani, Miriam Ziba (Il sogno della farfalla, 2018)
The author describes her therapeutic practice within a community for psychiatric patients. The main aspect of the therapeutic work is represented by the interpretation of the non-conscious relationship of the patient with the psychotherapist, and in particular, by the frustration of negative transference. Only this way is it possible to carry out a therapeutic practice that is aimed at the emergence of vitality, of the capability to imagine, of positive emotions and affections in patients thus making them overcome splitting and fragmentation that lie in their most hidden pathological dimensions.